Analisis Efektifitas Metode Weighted Product dan TOPSIS dalam Mendiagnosa Serangan Asma - Ade Ragil Purwandani; Ario Yudo Husodo; Fitri Bimantoro (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
To diagnose asthma attack we use Weighted Product and TOPSIS method to analyze the data. The lack of Weighted Product for the expert system is there are no cost and benefit for the criteria. We use combined it with TOPSIS to determining an alternative preference based on the ideal positive and ideal negative solution. WP methods have advantages where it has an initial weight which is TOPSIS don’t have. Combining the two methods aims to determine the effectiveness of the method. We use 40 data test on two different experts and compare it with our proposed method in this research. The result shows that, for the first expert, we gain accuracy for Weighted Product, TOPSIS and combined of WP and TOPSIS are 12,5%, 12,5%, and 60% respectively and for the second expert, we gain 30%, 30%, and 70%. Its show that the combined methods are better used compared to the WP and TOPSIS methods.